Process development for PETase production and purification - Raden Himan Haryo Teguh (Nanyang Technological University, 2024)
Plastic pollution is a critical global issue caused by the accumulation of plastic waste, leading to severe environmental impacts if not properly managed. Of the 350 million tonnes of plastic waste, 68.2% was disposed of at a landfill or incinerated, 15.5% was recycled, and 23.2% was mismanaged or littered. Polyethylene terephthalate (PET) is one of the most prominent components of plastic packaging waste. While the present mechanical and chemical recycling methods are inadequate to economically recycle mixed and contaminated PET wastes into high-quality recycled PET, a biological method using the enzyme PET hydrolase (e.g., PETase, cutinase) is being explored. One of the bottlenecks for PET hydrolase-based recycling is enzyme production. This study aims to investigate the production and purification of PETase – one of the most studied PET hydrolases. The production of PETase includes medium preparation, fermentation, and enzyme separation. The study hypothesizes that optimizing batch and fed-batch fermentation using an optimized method can achieve more than 2.75 genzyme/Lmedia and 90% or more purification efficiency in each purification step. A stirred tank fermenter with a maximum working volume of 5 L will be used to grow the SHuffle T7 E. coli strain transformed with pET-22b plasmid containing engineered PETase genes, STAR-PETase, inducible by isopropyl ß-D-1-thiogalactopyranoside (IPTG). Corn steep liquor (CSL) was identified as a potential media component to replace yeast extract and tryptone in LB media due to its low cost and excellent nutrient content. The E3 medium, which contains CSL, improved wild-type PETase (WT-PETase) production and matched STAR-PETase's production in the LB medium. Therefore, a CSL-containing medium can be a suitable replacement for the LB medium. Using E3 media instead of LB may reduce the media cost by 93.75%. Besides, STAR-PETase contains more cysteine and methionine residues that may make it more challenging to fold correctly, reducing its production yield. The effect of CSL, glucose, glycerol, and MgSO4 concentrations on STAR-PETase mass and volumetric yields was determined using the Placket-Burman design by producing the enzyme in a 150 mL medium using the Placket-Burman design. Glucose and CSL concentrations were selected for further optimization. A one-factor-at-a-time (OFAT) experiment was conducted by varying CSL and glucose concentrations between 0.5 to 10 g/L while keeping the rest of the media constant. The result suggests that STAR-PETase production fits a quadratic model with a maximum volumetric yield of 1.37 mg/L at 5.5 g/L CSL. A validation experiment is attempted by varying CSL concentration from 0.5 to 5.25 g/L. However, the results deviate from the model and are inconclusive because of the high variance encountered in these experiments. The unstable gene expression, hence protein production, may be due to plasmid instability, mRNA instability, inclusion body formation, and protein degradation. Attempts to scale up the experiment were conducted to examine the process's scalability. The study shows a similar deviation from earlier experiments, further supporting the instability of the protein expression. Overall, the plastic enzymatic depolymerization technology is still at the start of the development cycle. While the PETase enzyme is not economically viable, it shows potential and should be developed further. This study has demonstrated that corn-steep liquor can be an adequate substitute for yeast extract. It should be optimized further in a stirred tank bioreactor with greater control over critical process parameters.